On the Origin and Function of the Armenian Article ը - MKRTCHYAN, GARIK (Bulletin of Yerevan University B: Philology, 2021)
The article considers the problem of the origin of Armenian definite article ը. Observations show that the usage of the definite article ը in Armenian is the result of natural laws and inner development of the language. This can also be proved by the absence of etymological equivalents of this grammatical particle in sister languages of Armenian. The usage of article ը is the result of regular phonetic changes. In consequence of dropping of the final consonant ն, ը of the hidden syllable fulfils the function of an article.